Unmet Emotional Support Needs Among Diverse Patients with Colorectal Cancer. Issue 6 (June 2020) - Kapadia, Muneera R.; Veenstra, Christine M.; Davis, Rachel E.; Hawley, Sarah T.; Morris, Arden M.
Background: Social support, which is partly emotional support, is associated with adherence to colorectal cancer (CRC) treatment, quality of life, and survival. We hypothesized that the needs, sources, and availability of emotional support would vary by race and income among CRC patients and sought to quantify the emotional support and the perceived adequacy of support reported by patients. Methods: We surveyed CRC patients from Detroit and Georgia Surveillance, Epidemiology and End Results registries about the quantity and quality of emotional support received from different sources. We tested differences using the chi-square test, t -tests, and logistic regression. Results: There were 1909 patients who met inclusion criteria and 1301 (68%) completed surveys. Among respondents, 68% were white, 25% black, and 7% other. Black patients were more likely to be female and younger and reported lower annual income and education. Patients reported high support from several sources. Among those with a spouse/partner (58%), 95% reported high levels of support; however, older, black, female, or lower income patients were less likely to have spouses/partners ( P < .001). Patients also endorsed high support from family (88.6%), important others (82.9%), and clinicians (71.3%). Black patients were less likely than white patients to report support that was "just right" ( P < .001). Discussion: Most patients reported high emotional support from at least 1 source. Black patients were most at risk for low support or unmet support needs. Spouse/partner support was important but only available to 58% of respondents. Patients at risk for unmet emotional support needs may benefit from additional support resources.